Implementation of patient-reported outcome dashboards within the electronic health record to support shared decision-making in serious chronic illness - Glyn Elwyn; Sheetal M Kircher; Eugene Nelson; David Cella; Lisa Hirschhorn; Cynthia Barnard; Vikram Aggarwal; Jeffrey Linder; Sofia F Garcia; Aricca Van Citters; Mary O'connor; Laura M Perry; et al. (BMJ Open Quality)
Background Attending to patient-reported outcomes (PROs) using data visualisation dashboards could enhance shared decision-making (SDM) and care delivery for serious chronic illnesses. However, few studies have evaluated real-world strategies and resulting implementation outcomes of PRO dashboards.Method From June 2020 to January 2022, we implemented an electronic health record (EHR)-integrated PRO dashboard for advanced cancer and chronic kidney disease. Based on implementation science guidelines (eg, Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies, Reach, Effectiveness, Adoption, Implementation, Maintenance), we monitored use and captured adaptations in implementation strategies. Clinicians (n=7) and patients (n=30) responded to a 6-month survey that included appropriateness, acceptability, adoption and sustainability.Results Out of 1450 eligible patients, 748 (52%) completed at least one PRO invitation (reach). 37% of PRO questionnaire invitations (1421/3882) were completed (fidelity to PRO completion), with higher rates occurring when more implementation strategies were adopted. Among completed postvisit surveys from patients, 57% indicated that the dashboard was discussed at an eligible visit (fidelity to dashboard use). In the 6-month survey, patients endorsed the dashboard’s acceptability and appropriateness: 77% felt it frequently provided clear information and 63% felt it frequently met their needs. Most patients (77%) and clinicians (86%) valued the dashboard for increasing SDM, and 57% of clinicians endorsed the dashboard’s clinical sustainability.Discussion This pilot study demonstrated the clinical appropriateness, acceptability and feasibility of implementing an EHR-integrated PRO dashboard for advanced cancer and chronic kidney disease. Results also point to areas for improvement, including strategies to further support patient and clinician engagement, PRO completion and sustainability in real-world implementation.